MODEL GERAKAN NITROGEN PADA BUDIDAYA PADI (Oryza sativa) DENGAN METODE SRI (System Of Rice Intensification) - Andra Tersiana Wati; Kurnia Subekti (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2018)
Nitrogen is an essential macro nutrient for the plant growth. Fertilization is one of the method to added nitrogen for plant nutrition. Therefore, an efficient fertilization is important to the rice cultivation.This study aimed to describe nitrogen distribution and availability in root zone of rice plant under System of Rice Intensification (SRI). This study was conducted in the screenhouse of Biophysics Laboratory, Faculty of Agricultural Technology UGM. Silt loam soil was used for plant media and rice variety (IR-64) was planted on the experimental pot with size of 30 x 30 cm2 and 40 cm height. Experiments were conducted in two irrigation method : conventional and minimum water standing of the system of rice intensification (SRI) and two fertilization methods : organic and chemical fertilizer combined with manure. Movement of nitrat was observed based its movement in the root zone. Mathematical modelling was also applied through prediction of nitrate concentrations. This study resulted that concentration and distribution of nitrate in the different root zone (5 cm and 15 cm) was not significantly different. Combination fertilization with the depth of 15 cm, resulted that nitrate availability pattern between flooded irrigation and water efficient irrigation system shows a coincide pattern. The prediction result of nitrate concentration shows a tendency that is similar to the observation result of nitrate concentration.